PENERAPAN METODE OUTDOOR LEARNING TERHADAP KETERAMPILAN PROSES SAINS PADA MATERI KEANEKARAGAMAN HAYATI - Yunita, Erma; Ariyati, Eka; Yokhebed, Yokhebed (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Â Abstract This research aims to understand process science skill of students who had by using the method outdoor learning on the material biodiversity in the class ten grade science student of SMA Muhammadiyah 1 Pontianak. The research applied quasi-experimental method with non-equivalent control group design. Sample in this research was taken through intact group technique, where ten grade science three as the experimental class and ten grade science one as the control class. The instrument was a multiple-choice test consisting of 20 questions. The average value skill the process science of students at the experimental class was 16.07. Meanwhile, the average for control class was 13.67. Using U Mann-Whitney test, the research obtained -Zcount < -Ztable which was -4.29 < -1.96. This value means that there is a significant difference of skill the process science of students between students who use method outdoor learning and those who study conventionally.Keywords: Process Science skill of Students, Biodiversity, Outdoor Learning